Fabrication of Aluminium Polymer Nano Composite by In-Situ Technique - Prasad, Brijesh; Singh, Munna (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992927);" role="presentation">In the present work, <span dir="ltr" style="left: calc(var(–scale-factor)*163.94px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00361);" role="presentation">In-<span dir="ltr" style="left: calc(var(–scale-factor)*175.58px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933027);" role="presentation">situ <span dir="ltr" style="left: calc(var(–scale-factor)*195.05px); top: calc(var(–scale-factor)*304.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954039);" role="presentation">polymerization technique synthesized epoxy alumina polymer nanocomposite. <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937351);" role="presentation">Dispersion of alumina <span dir="ltr" style="left: calc(var(–scale-factor)*165.02px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910109);" role="presentation">nanoparticle <span dir="ltr" style="left: calc(var(–scale-factor)*217.61px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909526);" role="presentation">of rod shaped <span dir="ltr" style="left: calc(var(–scale-factor)*276.29px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887642);" role="presentation">and spherical shape <span dir="ltr" style="left: calc(var(–scale-factor)*358.75px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941876);" role="presentation">with size 20nm-<span dir="ltr" style="left: calc(var(–scale-factor)*424.03px); top: calc(var(–scale-factor)*317.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920825);" role="presentation">50nm, were achieved by <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938954);" role="presentation">ultra-<span dir="ltr" style="left: calc(var(–scale-factor)*93.62px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915831);" role="presentation">sonication <span dir="ltr" style="left: calc(var(–scale-factor)*139.46px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88724);" role="presentation">processing <span dir="ltr" style="left: calc(var(–scale-factor)*187.01px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899167);" role="presentation">technique. <span dir="ltr" style="left: calc(var(–scale-factor)*233.21px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96213);" role="presentation">Effect <span dir="ltr" style="left: calc(var(–scale-factor)*262.37px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963459);" role="presentation">on mechanical properties (Ten<span dir="ltr" style="left: calc(var(–scale-factor)*391.03px); top: calc(var(–scale-factor)*330.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956206);" role="presentation">sile and viscoelastic properties) <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894643);" role="presentation">because of <span dir="ltr" style="left: calc(var(–scale-factor)*119.30px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(–scale-factor)*135.26px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885451);" role="presentation">post <span dir="ltr" style="left: calc(var(–scale-factor)*155.66px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919889);" role="presentation">curing temperature <span dir="ltr" style="left: calc(var(–scale-factor)*236.45px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903412);" role="presentation">on <span dir="ltr" style="left: calc(var(–scale-factor)*250.25px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886569);" role="presentation">nanocomposites <span dir="ltr" style="left: calc(var(–scale-factor)*318.55px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88805);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*341.47px); top: calc(var(–scale-factor)*343.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921382);" role="presentation">determined. Postcuring temperatures 60, 80, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898797);" role="presentation">100, 120 and 1500 0<span dir="ltr" style="left: calc(var(–scale-factor)*152.78px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964639);" role="presentation">C w<span dir="ltr" style="left: calc(var(–scale-factor)*169.10px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911374);" role="presentation">ere selected. Tensile strength with <span dir="ltr" style="left: calc(var(–scale-factor)*308.69px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941461);" role="presentation">young’s <span dir="ltr" style="left: calc(var(–scale-factor)*343.63px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910002);" role="presentation">modulus, <span dir="ltr" style="left: calc(var(–scale-factor)*383.11px); top: calc(var(–scale-factor)*356.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900771);" role="presentation">and storage modulus of neat epoxy <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9642);" role="presentation">specimen as well as nanocomposite with different wt.% of nanoparticle <span dir="ltr" style="left: calc(var(–scale-factor)*376.39px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906186);" role="presentation">showed decrement <span dir="ltr" style="left: calc(var(–scale-factor)*457.06px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992626);" role="presentation">with <span dir="ltr" style="left: calc(var(–scale-factor)*478.78px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86902);" role="presentation">increase <span dir="ltr" style="left: calc(var(–scale-factor)*515.74px); top: calc(var(–scale-factor)*370.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886332);" role="presentation">temperature, <span dir="ltr" style="left: calc(var(–scale-factor)*129.80px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967907);" role="presentation">while <span dir="ltr" style="left: calc(var(–scale-factor)*159.31px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.858059);" role="presentation">glass <span dir="ltr" style="left: calc(var(–scale-factor)*186.78px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936122);" role="presentation">transition <span dir="ltr" style="left: calc(var(–scale-factor)*232.11px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.885684);" role="presentation">temperature <span dir="ltr" style="left: calc(var(–scale-factor)*287.26px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878543);" role="presentation">increased. <span dir="ltr" style="left: calc(var(–scale-factor)*335.21px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92127);" role="presentation">Mechanical <span dir="ltr" style="left: calc(var(–scale-factor)*389.19px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901571);" role="presentation">properties <span dir="ltr" style="left: calc(var(–scale-factor)*436.99px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">were <span dir="ltr" style="left: calc(var(–scale-factor)*464.02px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93486);" role="presentation">maximum <span dir="ltr" style="left: calc(var(–scale-factor)*511.86px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921334);" role="presentation">nanocomposite with <span dir="ltr" style="left: calc(var(–scale-factor)*156.02px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948011);" role="presentation">0.1 wt. % nanoparticle for all <span dir="ltr" style="left: calc(var(–scale-factor)*277.73px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905839);" role="presentation">Postcuring <span dir="ltr" style="left: calc(var(–scale-factor)*323.35px); top: calc(var(–scale-factor)*396.55px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906116);" role="presentation">temperature. It was observed that Nanocomposite <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899323);" role="presentation">with rod shape showed <span dir="ltr" style="left: calc(var(–scale-factor)*166.46px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899455);" role="presentation">good mechanical <span dir="ltr" style="left: calc(var(–scale-factor)*236.81px); top: calc(var(–scale-factor)*409.87px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903319);" role="presentation">properties.